Cardiovascular health in menopause. - Medina, Félix (2015)
Cardiovascular risk is poorly managed in women, especially during the menopausal transition when susceptibility to cardiovascular events increases. Clear gender differences exist in epidemiology, symptoms, diagnosis, progression, and management of cardiovascular risk. Key risk factors to be controlled in the peri-menopausal woman are hypertension, dyslipidemia, obesity, and other components of the metabolic syndrome, with the avoidance and careful control of diabetes. Hypertension is a particularly powerful risk factor and lowering of blood pressure is pivotal. There are some scores for risk stratification and Reynolds’ is of relevant significance. Team work is of extreme importance in the optimal risk cardiovascular stratification in women, moreover in the perimenopausal period.